2023
DOI: 10.1039/d2sm01229d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the polar group content on the glass transition temperature of ROMP copolymers

Abstract: Polar groups have long been recognized to greatly influence the glass transition temperature (Tg) of polymers, but understanding the underlying physical mechanism remains a challenge. Here, we study the glass...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 71 publications
1
11
0
Order By: Relevance
“…The same conclusion has been drawn in a previous study of the Stockmayer fluid in which the interacting particles exhibit both LJ and charge (dipole) interactions . In the corresponding case of polymeric liquids, Li et al have found that the cohesive energy density of a coarse-grained polar polymer melt increases linearly with increasing the polar group content, and our previous work has likewise indicated that the cohesive energy density increases with increasing the charge interaction strength . Our simulation results indeed suggest that glass formation in charged polymers at least roughly corresponds to uncharged polymers with a modified short-range attractive interparticle interaction strength ϵ LJ , supporting our hypothesis that the effective LJ interaction is renormalized by the charge interactions.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The same conclusion has been drawn in a previous study of the Stockmayer fluid in which the interacting particles exhibit both LJ and charge (dipole) interactions . In the corresponding case of polymeric liquids, Li et al have found that the cohesive energy density of a coarse-grained polar polymer melt increases linearly with increasing the polar group content, and our previous work has likewise indicated that the cohesive energy density increases with increasing the charge interaction strength . Our simulation results indeed suggest that glass formation in charged polymers at least roughly corresponds to uncharged polymers with a modified short-range attractive interparticle interaction strength ϵ LJ , supporting our hypothesis that the effective LJ interaction is renormalized by the charge interactions.…”
Section: Resultssupporting
confidence: 90%
“…Dashed−dotted lines are fits to the linear equation T x (P) = T x (0) + a x P with x = A, c, g, or 0, where the fitting parameters (a A , a c , a g , a 0 ) are determined to be 6.66 × 10 −2 , 3.24 × 10 −2 , 2.86 × 10 −2 , and 2.61 × 10 −2 and 6.00 × 10 −2 , 3.83 × 10 −2 , 3.52 × 10 −2 , and 3.00 × 10 −2 for uncharged and charged polymer melts, respectively. of polymeric liquids, Li et al 86 have found that the cohesive energy density of a coarse-grained polar polymer melt increases linearly with increasing the polar group content, and our previous work has likewise indicated that the cohesive energy density increases with increasing the charge interaction strength. 24 Our simulation results indeed suggest that glass formation in charged polymers at least roughly corresponds to uncharged polymers with a modified short-range attractive interparticle interaction strength ϵ LJ , supporting our hypothesis that the effective LJ interaction is renormalized by the charge interactions.…”
Section: T H I S C O N T E N T Imentioning
confidence: 62%
See 1 more Smart Citation
“…The presence of polar functional groups is known to affect mechanical properties and increase glass transition temperatures for many types of polymer materials . In order to separately consider the polar effects resulting from installation of the ketone with any effects that are specific to the vinyl C–H hydrogen bond, we prepared a control polymer in which the ketone was maintained but the conjugated alkene was removed.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of polar functional groups is known to affect mechanical properties and increase glass transition temperatures for many types of polymer materials. 53 In order to separately consider the polar effects resulting from installation of the ketone with any effects that are specific to the vinyl C−H hydrogen bond, we prepared a control polymer in which the ketone was maintained but the conjugated alkene was removed. As shown in Scheme 3, the control polymer (oxaPDCPD RD ; 5 p ) was efficiently synthesized through regioselective zinc-promoted reduction of the enone monomer (4 m ) 54 followed by polymerization with the Grubbs second-or third-generation catalyst.…”
Section: Computational Analysis and Comparison To Experimental Datamentioning
confidence: 99%